Effect of the carrier solution for hydroxyethyl starch on platelet aggregation and clot formation - Schaden, E.; Wetzel, L.; Kozek-Langenecker, S.; Thaler, U.; Scharbert, G. (British journal of anaesthesia : BJA, 2012)
Hydroxyethyl starch (HES) solutions alter blood coagulation, mainly platelet function and fibrinogen polymerization. Haemostasis can also be impaired by dilutional-hyperchloraemic acidosis induced by the HES carrier solution. We hypothesized that a saline-based tetrastarch carrier solution impairs parameters of blood coagulation more than a balanced carrier solution. The study was designed as a prospective, double-blinded, randomized, cross-over trial in healthy male volunteers. At intervals of at least 10 days, 13 subjects received 20 ml kg−1 of balanced or saline-based tetrastarch over 2 h. Blood was subjected to blood gas analysis, assessment of platelet function [with multiple electrode aggregometry (MEA)], and clot formation (with rotational thrombelastometry). Maximum aggregation in response to adenosine diphosphate (ADP) decreased after saline-based HES infusion, but not after balanced solution-based HES infusion. ADP-induced platelet aggregation was significantly lower after saline-based HES compared with baseline (21%; P<0.025) and compared with balanced solution-based HES (17%; P<0.025). There were no significant changes in platelet aggregation induced by thrombin receptor-activating peptide and in any parameter of rotational thrombelastometry. Chloride concentrations were significantly higher after saline-based HES compared with balanced solution-based HES. The carrier solution for HES up to 20 ml kg−1 had little impact on platelet aggregation or clot formation as assessed by MEA and rotational thrombelastometry, respectively. Further clinical studies are required to verify this finding in patients and to correlate results of whole blood aggregometry and rotational thrombelastometry with perioperative bleeding and transfusion requirements.